The Subject of Da'wah in the Koran and Its Role in the Digital Era - Nasrillah, Nasrillah; Harmen, Harmen; Ayu, Zelda Puspa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Da'wah using digital provides space for preachers to convey the teachings of the Islamic religion in today's era. The aim of this research is to find out how to preach in today's digital era. This research method uses literature study. This technique is carried out by collecting data and reading the data as well as collecting various literature and references related to the research content. This research explains how to preach in the digital era.